Hormonal management of menopausal symptoms in women with a history of gynecologic malignancy. Issue 2 (February 2020) - Harris, Benjamin S.; Bishop, Katherine C.; Kuller, Jeffrey A.; Ford, Anne C.; Muasher, Lisa C.; Cantrell, Sarah E.; Price, Thomas M.
Abstract: Objective: The aim of the study was to review the role of hormone therapy in menopausal patients with breast cancer and gynecologic malignancies. Methods: We searched MEDLINE (via PubMed) using a combination of keywords and database-specific subject headings for the following concepts: menopause, hormone therapy, and cancer. Editorials, letters, case reports, and comments were excluded, as were non-English articles. Additional references were identified by hand-searching bibliographies of included articles. The searches yielded a total of 1, 484 citations. All citations were imported into EndNote X9, where they were screened by the authors. Results: In breast cancer survivors, systemic hormone therapy is not recommended, whereas local low-dose estrogen therapy may be considered after discussion with the patient's oncologist. Among endometrial cancer survivors, hormone therapy is considered safe in low-risk cancers but should be avoided in high-risk subtypes. For survivors of epithelial ovarian cancer and cervical cancer, hormone therapy can be considered, but should be avoided in women with estrogen-sensitive histologic subtypes. Conclusions: The risks of hormone therapy should be assessed on an individual basis, with consideration of age, type of hormone therapy, dose, duration of use, regimen, route, and prior exposure. Systemic hormone therapy is not recommended in breast cancer survivors, whereas vaginal low-dose estrogen appears safe. Hormone therapy may be used by endometrial, cervical, and ovarian cancer survivors with low-risk, non-estrogen-receptor–positive subtypes. Video Summary: http://links.lww.com/MENO/A516 . Abstract : Supplemental Digital Content is available in the text